Pertanggungjawaban Pidana dalam Pelaksanaan Kewenangan Kepolisian - Ismansyah, Ismansyah (Jurnal Demokrasi, 2008)
The Indonesian Policemen is an instrument which plays a significant role in maintaining integrity and peacefulness in a society, maintaining law and giving the protection for nation, guardianship, and ready to give the best service for society in order to create the safety and orderliness in this country. However, we cannot deny that the work of the police officers apparatus was still not maximal yet. It needs to be improved and increased. Therefore, the policy of criminal control in overcoming improperly apparatus duty must be done as soon as possible. Kata Kunci: Upaya Paksa, Â Profesionalisme, Kode Etik